2020
DOI: 10.18203/issn.2455-4510.intjresorthop20202700
|View full text |Cite
|
Sign up to set email alerts
|

A rare case: exostosis of right foot

Abstract: <p>Exostosis is benign tumor. Osteochondromas are benign metaphyseal osseous growths occurring in long bones of body.  They contain cartilaginous cap which are present before closure of physis plate. Growth of these structures ends with physis fusion. Being benign in nature, they don’t require any surgery. Unless and until they cause compression symptoms on nerves and blood vessels, difficulty in movements of joints, and patients request for cosmetic appearance. Here by we present a rare case of 19 years… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…About 77% patients had flexion of >100°, while 23% patients had <100° of flexion. 14 In our study, out of 50 cases two cases (one case of distal femur fracture and one case of proximal tibia fracture) went into non-union and three cases developed superficial wound infection in our study which subsided by wound dressing and intravenous antibiotic treatment, no case required further surgery. The study by Yeap and Deepak who used LCP fixation for DF fractures without fibula graft found complication in 11 cases which included one implant fracture which required revision to another DF-LCP surgery.…”
Section: Discussionmentioning
confidence: 45%
“…About 77% patients had flexion of >100°, while 23% patients had <100° of flexion. 14 In our study, out of 50 cases two cases (one case of distal femur fracture and one case of proximal tibia fracture) went into non-union and three cases developed superficial wound infection in our study which subsided by wound dressing and intravenous antibiotic treatment, no case required further surgery. The study by Yeap and Deepak who used LCP fixation for DF fractures without fibula graft found complication in 11 cases which included one implant fracture which required revision to another DF-LCP surgery.…”
Section: Discussionmentioning
confidence: 45%